THERMAL-STABILITY OF 2ND-ORDER NONLINEARITY IN POLED POLYMERIC FILMS - HUANG, JY; LIAO, CL; WHANG, WT; CHANG, CJ (My University, 1995)
The thermal stability of the poled polar order of nonlinear optical (NLO) chromophores covalently appended to the main chain of polymeric films was studied by measuring the generated optical second-harmonic signal over a wide range of temperatures. Our results provide insight into the relationship of the thermal stability of the poled order with chemical bonding and elastic interaction of the NLO chromophores in polymeric matrices.
Keywords: NONLINEAR OPTICAL POLYMER; THERMAL STABILITY; POLAR ORDER; 2ND-HARMONIC GENERATION; ELASTIC INTERACTION